Cat Ballou [videorecording (Blu-Ray)] - Newman, Walter; Pierson, Frank R.; Chanslor, Roy, 1899-1964; Fonda, Jane, 1937-; Marvin, Lee; Callan, Michael, 1935-2022; Hickman, Dwayne (Sony Pictures Home Entertainment, 2024)
The sleeper hit of 1965, Cat Ballou was declared an instant classic when its sly blend of Western parody and rapid-fire action hit the screen. Lee Marvin won an Oscar for Best Actor for his dual role as nose less ("It got bit off in a fight") gunslinger Tim Strawn and as Kid Shelleen, the woozy, boozy has-been who goes up against him. Jane Fonda co-stars as Catherine "Cat" Ballou, the schoolmarm-turned-outlaw who teams up with Kid. Singer Nat King Cole and comedian Stubby Kaye also appear, singing the title song, "The Ballad of Cat Ballou."